Choosing Healthy Meals As You Get Older: 10 Healthy Eating Tips for People Age 65+ - Linda Bobroff (EDIS, 2017)
After introducing MyPlate in June 2011, USDA provided a series of fact sheets to help consumers use the dietary advice of the Dietary Guidelines 2010. USDA continues to add fact sheets to the series, reflecting the most current Dietary Guidelines and issues important to consumers. This fact sheet was developed by the Center for Nutrition Policy and Promotion/USDA in partnership with the National Institute on Aging/National Institutes of Health. This series of fact sheets is distributed by UF/IFAS Extension, June 2017.